2022
DOI: 10.1002/aet2.10835
|View full text |Cite
|
Sign up to set email alerts
|

Educator's blueprint: A how‐to guide for collecting validity evidence in survey‐ based research

Abstract: Surveys are descriptive assessment tools. Like other assessment tools, the validity and reliability of the data obtained from surveys depend, in large part, on the rigor of the development process. Without validity evidence, data from surveys may lack meaning, leading to uncertainty as to how well the survey truly measures the intended constructs. In documenting the evidence for the validity of survey results and their intended use, it is incumbent on the survey creator to have a firm understanding of validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…Following survey best practices, we began by assembling a group of experts in residency leadership and scheduling to develop content validity. 7,8 We conducted a literature search to identify existing survey tools. Finding no ideal tool for this, we developed a tool informed by these existing studies and current needs identified by the group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following survey best practices, we began by assembling a group of experts in residency leadership and scheduling to develop content validity. 7,8 We conducted a literature search to identify existing survey tools. Finding no ideal tool for this, we developed a tool informed by these existing studies and current needs identified by the group.…”
Section: Methodsmentioning
confidence: 99%
“…We performed a cross‐sectional survey study regarding scheduling practices for EM residents in the United States. Following survey best practices, we began by assembling a group of experts in residency leadership and scheduling to develop content validity 7,8 . We conducted a literature search to identify existing survey tools.…”
Section: Methodsmentioning
confidence: 99%
“…Then, pilot test the tool on a meaningful sample of applications (e.g., 30 applications) with all reviewers. Consider using strategies such as “think‐aloud” or cognitive interviewing to solicit understanding of how reviewers interpret the questions 21 . Use this process to develop and refine your initial system and then solicit continued feedback throughout the process.…”
Section: Ten Strategiesmentioning
confidence: 99%
“…Prior to full deployment, it is helpful to pilot the tool with a meaningful sample of files to assess response process validity (i.e., the tool is being interpreted as intended) and ease of use in a range of different circumstances. 21 Begin by reviewing the tool as a small group to ensure all questions are clearly written with appropriate rating options and anchors. 22 Then, pilot test the tool on a meaningful sample of applications (e.g., 30 applications) with all reviewers.…”
Section: Pilot Test the Review Process With A Purposeful Sample Of Ap...mentioning
confidence: 99%
“…Given the complexity of survey‐based medical education research, our intention with this series was to simplify the process of conducting survey research within academic emergency medicine 1,2 . Our goal was to improve the approach to survey methodology; as such, we sought to develop a series of best practices articles as a guide for medical education researchers.…”
Section: Introductionmentioning
confidence: 99%